APPLICATION OF A CONTEXTUAL APPROACH IN HISTORY LEARNING TO ENCOURAGE STUDENTS' CRITICAL THINKING AT SMA NEGERI 1 MEDAN - Hayati, Rina Purna; Sumantri, Pulung; Arif, Toni (Department of History Education, Faculty of Social Science, Universitas Negeri Medan, 2024)
History education has an important role in shaping students' understanding of the past and its relationship to the current context. However, challenges arise in teaching history in a way that encourages students to think critically and relate learning to contemporary realities. This research aims to explore the application of a contextual approach to history learning at SMA Negeri 1 Medan in an effort to strengthen students' critical thinking skills. The research method used is a case study using interviews, observation and document analysis as data collection techniques. The research results show that the application of a contextual approach to history learning has succeeded in activating students to think critically, increasing their involvement in the learning process, and strengthening the relationship between historical material and the current social, cultural and political context. The implication of these findings is the need to continue to encourage innovation in history learning approaches to produce a generation that is critical, informed, and able to relate learning to the realities they face.